Building a thriving forage seed sector in Vietnam - Dao Thu, Hang Thi; Peters, Michael; Tran, Thi Bich Ngoc; Burkart, Stefan; Atieno, Mary (2025)
Livestock production is a vital contributor to both the economy and food security of Vietnamese households. As Vietnam continues to intensify and transform its livestock sector, the persistent challenge of feed scarcity—both in quantity and quality—remains a major bottleneck to productivity, profitability, and climate resilience. Shortage of high-quality forages continue to constrain animal nutrition and overall livestock productivity, particularly during seasonal scarcity. Strengthening forage seed systems is therefore essential to support more resilient and efficient livestock systems, which can contribute to improved resource use and reduced environmental impacts. In this context, the Tropical Forages Program (TFP) of the Alliance of Bioversity International and CIAT, in partnership with the National Institute of Animal Science (NIAS) and key actors in the forage seed sector, held a national stakeholder meeting on June 24, 2025, in Hanoi. The meeting aimed to build a common understanding of the opportunities and challenges in Vietnam’s forage seed sector and to promote collaborative action toward a more dynamic forage seed system.